DEVELOPMENTS IN THE UNDERSTANDING AND APPLICATION OF LITHIUM ISOTOPES IN THE EARTH AND PLANETARY SCIENCES - Tomascak P.B. (My University, 2004)
The significant relative mass difference (c. 16%) between the two stable isotopes of Li (approximately 6Li 7.5%, 7Li 92.5%), coupled with broad elemental dispersion in Earth and planetary materials, makes this a system of considerable interest in fingerprinting geochemical processes, determining mass balances, and in thermometry. Natural mass fractionation in this system is responsible for c. 6% variation among materials examined to date (Fig. 1⇓). Although the “modern era” of Li isotope quantification has begun, there are still many questions about the Li isotopic compositions of fundamental materials and the nature of fractionation by important mechanisms that are unanswered (e.g., Hoefs 1997). Figure 1. Summary of lithium isotopic compositions of Earth and planetary materials. Filled bars are solid samples, open bars are liquids. See text for references and details. The purpose of this chapter is to summarize the current understanding of Li isotopes in geo- and cosmochemical systems and to indicate (1) where Li isotopes have a high probability of adding new understanding of these systems; (2) where some of the more significant deficits in knowledge exist. The small but burgeoning Li isotope community has not yet compiled the volume of peer-reviewed literature needed to adequately assess even that which has been studied to date. As a result, significant portions of this chapter are based on data reported in abstracts, and as such are more than normally subject to revisions over time. This chapter is anticipated to serve as a starting point for those interested in research incorporating Li isotope geochemistry, or in understanding the state of extant research. ### Experiments in Li isotope fractionation​